PENGARUHLEVERAGE TERHADAPVOLATILITAS RETURNPADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mimi Oktariza Putri (JURNAL PUNDI, 2020)
Fast traslate Icon translate Basically, every company has a goal to maintain the company and develop its business in order to obtain a return. In maintaining the company's return depends on how the company's ability to bear risk. The higher the risk taken, the greater the expected return received. The study was conducted to increase knowledge about the effect of leverage on return volatility. Population are companies listed on the Indonesia Stock Exchange at the end of the 2018 observation period. The sample collection technique has been carried out using a purposive sampling method with 14 companies selected as samples. The analytical method used is panel data regression analysis, in this method observations were made from 2014 - 2018 and obtained 70 observations. This study shows that leverage has a positive and significant effect on return volatility.